AKTIVITAS KOMBINASI EKSTRAK BAWANG DAYAK-METFORMIN TERHADAP GULA DARAH MENCIT - Aditya Maulana Perdana Putra; Ratih Sari Pratiwi (Jurnal Ilmiah Manuntung, 2018)
Diabetes mellitus is a chronic disease that requires good medical treatment to prevent long-term complications. The proportion of DM patients in Indonesia in 2013 was 3,7 million. Indonesia as one of the countries with the highest diversity has natural resources that can be used as an alternative medicine for diabetes mellitus, one of them is dayak onion. Dayak onions themselves contain compounds that can reduce blood glucose levels. The use of traditional medicine in the community is sometimes combined with chemical drugs. So the purpose of this study was to determine the comparison of the combination activity of dayak onion extract – metformin with single metformin to reduce mice blood sugar induced by alloxan. This research includes experimental research. The test animals used were male white mice which were divided into 2 groups, namely the combination of dayak onion and metformin and the single metformin group. The dose of dayak onion extract used in this study was 100 mg / KgBB and the dose of Metformin used was 45 mg / KgBB. Measurement of glucose levels is carried out every 3 days for 15 days. The decrease in fasting blood glucose from the control group and the test group was analyzed by the General Linear Model test at a 95% confidence level. The results of this study indicate that the combination of dayak onion tuber extract and metformin has better hypoglycemic activity than single metformin. This result can be seen from the average glucose level from day 3 to 15 the combination of dayak onion tuber and metformin is lower than the average glucose level of single metformin. The results of GLM analysis showed the sigvalue <0,05 so it can be concluded that there is a difference in glucose levels between the combination of dayak onion tuber and metformin with a single metformin.